2000
DOI: 10.1007/s001060050036
|View full text |Cite
|
Sign up to set email alerts
|

Chronisch rezidivierende Parotitis des Kindesalters bei eineiigen Zwillingen Magnetresonanzsialographie

Abstract: Recurrent parotitis is rare in childhood. Its occurrence is characterized by recurrent episodes of swelling and pain in the parotid gland, which are usually accompanied by fever and malaise. Inflammation usually resolves spontaneously during adolescence. The disorder is a condition of unknown etiology. Sialectasis and stricturing occurs in the distal ducts, whereas inflammation of the gland and duct epithelium is probably caused by a low salivary flow rate. Which one can be considered the primary event or seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 17 publications
(20 reference statements)
0
2
0
1
Order By: Relevance
“…Familial disease, in the sense of an autosomal dominant inheritance, has frequently been reported in the literature [ 18 ]. Wittekindt et al published a case report relating to this, which involved identical twins with chronic recurrent parotitis in childhood [ 130 ]. Reid et al reported a family where four members had the disease and two others had asymptomatic changes [ 131 ].…”
Section: Salivary Gland Infection/inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Familial disease, in the sense of an autosomal dominant inheritance, has frequently been reported in the literature [ 18 ]. Wittekindt et al published a case report relating to this, which involved identical twins with chronic recurrent parotitis in childhood [ 130 ]. Reid et al reported a family where four members had the disease and two others had asymptomatic changes [ 131 ].…”
Section: Salivary Gland Infection/inflammationmentioning
confidence: 99%
“…MRI and MR sialography are excellent ways of visualising salivary gland parenchyma as well as the excretory ducts. The latter can be seen without contrast enhancement in a special T2 weighting [ 130 ]. With alternative methods available, however, the time and effort required for this type of imaging in children mean that it is only worth considering for paedriatric patients in exceptional cases.…”
Section: Salivary Gland Infection/inflammationmentioning
confidence: 99%
“…Dies wurde auch in der Literatur bereits in Einzelfällen beschrieben [13]. Neuere Studien konnten durch Sialographie oder Magnetresonanzsialographie die Hypothese stützen, dass dieses Krankheitsbild vor allem auf kongenitalen Abnormitäten des Gangsystems beruht [21]. Neuere Studien konnten durch Sialographie oder Magnetresonanzsialographie die Hypothese stützen, dass dieses Krankheitsbild vor allem auf kongenitalen Abnormitäten des Gangsystems beruht [21].…”
Section: Sterile Abszesseunclassified